Evaluating the effectiveness of bupropion and varenicline for smoking cessation using an internet-based delivery system: A pragmatic randomized controlled trial (MATCH study). (1st March 2022) - Zhang, Helena; Mansoursadeghi-Gilan, Tara; Hussain, Sarwar; Veldhuizen, Scott; Le Foll, Bernard; Selby, Peter; Zawertailo, Laurie
Abstract: Background: Traditional randomized controlled trials have demonstrated the efficacy of pharmacotherapy for smoking cessation. However, accessibility to treatments remains a barrier, necessitating the remote delivery of evidence-based cessation interventions. The aim of this study was to evaluate the effectiveness of an online treatment that included first-line prescription medications using a pragmatic randomized controlled trial design. Methods: This study was a two-group, parallel block randomized, open label, controlled trial, and conducted exclusively online. Participants were randomised (1:1) to either bupropion (150 mg) or varenicline (1 mg) for twelve weeks. Medication was couriered to participants. The primary outcome was 7-day point prevalence abstinence (PPA; defined as 0 cigarette puffs in the last 7 days) at 12 weeks. Secondary outcomes were 7-day PPA at 4-, 8-, 26-, and 52-weeks follow-up. Adverse events were evaluated at each follow-up session during treatment. Results: The varenicline group (n = 499) had significantly higher 7-day PPA (30.3%) compared to the bupropion group (n = 465; 19.6%) at end of treatment (OR=2.08, 95% CI: 1.49–2.90, p < 0.001). Seven-day PPA was also higher for the varenicline group at 4-weeks (OR=1.71, 95% CI: 1.23–2.40 p = 0.0001), and 8-weeks follow-up (OR=1.95, 95% CI: 1.43–2.67 p < 0.0001), but not at post-treatment follow-up. More adverse events were reported in the varenicline group, compared to bupropion. Conclusions: This internet-based pharmacotherapy intervention was a feasible and effective method of treatment delivery for smoking cessation. This method can be used to increase the accessibility and availability of cessation interventions, decreasing the burden of smoking-related diseases. Trial registration: This trial was registered with clinical trials.gov under NCT02146911. Registered 26 May 2014, https://clinicaltrials.gov/ct2/show/NCT02146911 Highlights: First internet-based trial for smoking cessation using prescription medication. Varenicline was more effective than bupropion for quitting at end of treatment. Both medications were safe and well-tolerated throughout the treatment. Both pharmacotherapies had comparable effectiveness compared to traditional trials.